쉽싸리의 기내 마디배양 시 탄소급원의 종류와 농도가 식물체 재분화 및 증식에 미치는 영향 - 이나념; 김지아; 김용욱; 김태동; Lee, Na-Nyum; Kim, Ji Ah; Kim, Yong Wook; Kim, Tae Dong (Journal of plant biotechnology, 2018)
We examined the effect of carbon sources on the regeneration and ex vitro acclimatization of Lycopus lucidus Turcz. ex Benth. Plantlets were regenerated on the 1/2MS medium supplemented with different concentrations (3 ~ 10%) of sucrose and glucose. The sucrose concentrations of 3% and 5% that were supplied enhanced shoot multiplication and rooting but hampered high concentration growth (including the length of the shoot and root). During ex vitro acclimatization, the tuberization of the root, the root length, the shoot length and the survival rate of Lycopus lucidus plantlets grown using 3% and 5% sucrose were found to be better than the other carbon sources and concentrations. Thus a sucrose concentration of 3% and 5% in the 1/2MS medium appeared to be better for both in vitro growth and ex vitro acclimatization of Lycopus lucidus. 본 연구에서는 쉽싸리의 재분화와 순화에 영향을 주는 탄소급원의 효과에 관한 연구를 수행하였다. 식물체 재분화는 1/2MS 배지에 3 ~ 10%의 sucrose와 glucose를 각각 다른 농도로 처리하여 재분화를 유도하였다. 그 결과 3%와 5% sucrose 처리에서 줄기증식과 발근이 증가되었으며, 고농도 처리에서는 줄기와 뿌리 길이 등의 생육이 억제되었다. 기외 순화 중 3% 혹은 5% sucrose 처리 배지에서 생육한 식물체의 뿌리비대, 뿌리길이, 줄기 길이 및 생존율은 glucose 및 다른 농도처리와 비교하여 가장 높게 나타났다. 따라서 3% 및 5% sucrose 처리는 쉽싸리의 기내 생육과 순화를 위해 가장 적정한 농도로 확인되었다.